Deexcitation Probabilities of Ne(3P2) by Kr for the Case E << D - Khadka, Deba Bahadur (Journal of Nepal Chemical Society, 2009)
The deexcitation probability calculation of the total Penning ionization cross section for Ne(3P2) by Kr has been made in the region of the collisional energy from 18.5 to 38.1 meV. Considering the magnitude of the mean collisional energy with respect to D, the application of the analysis in the case E >> D is expected to be more appropriate than in the case E << D. Theoretical investigations of Ne(3P2) by Kr for the case E >> D are also needed. Keywords: metastable atoms, resonance atoms, deexcitation cross sections, pulse radiolysis, impact parameter. DOI: 10.3126/jncs.v24i0.2390 Journal of Nepal Chemical Society Vol.24 Page 45-48